Fiscal Implications of Government Wage Bill Spending - Dybczak, Kamil (IMF Working Papers; Working Paper ;, 2019)
This paper discusses the short- and medium-term fiscal implications of government wage bill spending. Working with a sample of 137 advanced, emerging and low-income countries, we use a panel VAR approach to identify differences in the dynamic behavior of revenues, nonwage expenditures, and the overall fiscal balance in response to changes in the wage bill. We show that the interaction between wage bill changes and these three fiscal items is alike and varies overtime. Higher wage bill spending does not revert in the medium term, but the initial worsening of the fiscal balance associated with it, though it persists, eventually halves as revenues increase while non-wage spending remains broadly unchanged. We also show that countries differ in how these three fiscal variables behave following wage bill changes and seek to explain this variation by a set of country characteristics, including the level of development, access to natural resources and public indebtedness levels.